The Effect of Eliminating of Fertiliser Subsidy Policy on Pepper Farmers inKundi Village, Simpang Teritip Sub-district - Leno Seftian Saputra; Rostiar Sitorus; Novyandra Ilham Bahtera (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Kelautan Universitas Bangka Belitung, 2026)
This study aims to analyze the effect of the elimination of fertilizer subsidy policy on the total income of pepper farmers in Kundi Village, Simpang Teritip District. The research method used is a survey method with paired sample t-test analysis. The survey method used as a research technique whose implementation is through interview guidelines, questionnaires or by telephone. The sampling method uses non-probability sampling with purposive sampling. Based on several samples that meet the criteria or characteristics of pepper farmers in Kundi Village in this study, there are 30 samples. The data processing method uses Microsoft Excel and SPSS version 25. The results of the study show that the total income of pepper farmers in Kundi Village, Simpang Teritip District before the elimination of the fertilizer subsidy policy was Rp. 332,326,420, then after the elimination of the fertilizer subsidy policy was Rp. 205,262,560 there was a significant difference, in the paired sample t-test the significance value was 0.00.